PTH-095 Decision drivers in Crohn's disease management with biologics in the NHS: A national Consensus view. (June 2019) - Hoque, Sami; Jones, Sue; Gwynn, Simon; Warren, Tim; Patel, Pritash
Abstract : Introduction: Crohn's disease is an idiopathic chronic inflammatory bowel disease without a cure. About 50% of Crohn's disease is progressive, leading to intestinal complications and surgery in about 30% of cases, 20-years post-diagnosis. Despite, existence of several guidelines, there are considerable variations in practice among practicing Gastroenterologist in the UK. In addition, the lack of reliable biomarkers prevent personalised treatment plans for complex cases of Crohn's disease, resulting in a degree of experimentation to establish therapeutic strategy. This project aims to gain insight from practicing gastroenterologists around the UK regarding these issues, to review variation across the UK and offer appropriate recommendations. Methodology: This group met to consider the various issues affecting the clinical management of Crohn's disease and develop of a series of 40 consensus statements that could be tested by questionnaire. Respondents were engaged by telephone contact and screened for their specialty and involvement with the prescribing of biologics. In order to achieve consensus with the wider group, a Delphi methodology was used. The steering group predefined the threshold of agreement for consensus at 66% and over. Consensus was defined as 'high' at ≥66% and 'very high' at ≥90%. Results: Fully completed questionnaires were received from 150 respondents. Each response was coded as either agreement or disagreement, with 24 statements (60%) exceeding the 66% agreement threshold and 16 statements (40%) failing to meet it. Five statements (13%) achieved agreement scores greater than 90% and indicated very strong consensus. Responses were received from across the UK, with the greatest number being from England. Clear variation was seen between respondents when the different localities were compared. Discussion: There are clear differences amongst respondent attitudes in London and other UK areas, including England. All respondent groups strongly support the need for biologic therapy to be used first line for certain patient groups (83.3% agreement). All respondents support the assertion that the principles for switching between originator and biosimilar should be defined by gastroenterologists (90.5% agreement) and that patients should be consulted before being switched to a different biosimilar option (74% agreement).